Participative design of an interactive system for the social appropriation of the Cultural Landscape Colombian Coffee grower (2019)
The following text aims to lay some foundations of participatory design, to create aframework that allows the projection of interactive systems, where information,communication and interaction, are variables involving social appropriation ofcultural heritage the inhabitants of a territory, which involves defining, or at least putunder discussion, new and better ways of design of these systems, compared to thetransverse dimensions that compose framed in possible contextual sensitivities.